Differences in Dry Matter Accumulation and Distribution Patterns between Pre-Elite Seed and Certified Seed of Virus-Free Potato - Chao Wu; Haiyan Ma; Xiaoting Fang; Ruilin Liu; Xinxin Shi; Kaiqin Zhang; Qiang Wang; Shunlin Zheng (Horticulturae, 2023)
Virus-free seed potatoes are generally divided into pre-elite seeds and certified seeds. To study the differences in dry matter accumulation and distribution between pre-elite seeds and certified seeds through a field randomized block two-factor experiment, pre-elite seeds and certified seeds of four varieties were selected to explore the differences in growth characteristics between the two levels of virus-free potatoes and to find a way to improve potato seed expansion efficiency. The results showed that the growth process of pre-elite seeds was slower and the growth period was longer than certified seeds. The dry matter accumulation of pre-elite seeds in various organs was lower than in certified seeds, and the distribution ratio in the roots and stems of each variety was also lower than the certified seed, while there was no significant difference in the leaf and tuber distribution ratio. The average dry matter accumulation rate in both pre-elite and certified seeds was sorted by size of tubers > leaves > stems > roots; however, it was significantly lower in pre-elite seeds than in certified seeds. Tuber fresh weight, tuber volume, tuber number, and the theoretical yield of certified seeds were higher than those of pre-elite seeds. Experiments have shown that appropriately prolonging the harvest time of virus-free potatoes, especially pre-elite seeds, and increasing the proportion of dry matter allocated to roots and stems by pre-elite seeds in the early growth stages can effectively increase yield.